International business and the necessity to learn language and culture - Tang, Sze Jun (2024)
This research is aimed to investigate the factors that influence user acceptance of Neobanks in Malaysia. This research uses five variables (perceived usefulness, perceived ease of use, perceived security, perceived low cost, and financial literacy) to determine the correlation with the user acceptance of Neobanks by referring TAM model and financial literacy framework. This study involved 200 Malaysian young adults (18-31 years old) as target respondents who were enough age to open Neobanks account. Data collection will be done via questionnaires on Google Forms for an easier, faster, and more contactless method to collect data during the pandemic. The collected data will be analysed by SPSS software. SPSS software is applied to conduct Cronbach's Alpha, and Multiple Regression Analysis. The results concluded that perceived usefulness, perceived ease of use, and perceived security have a significant relationship towards the user acceptance of Neobanks. However, perceived low cost and financial literacy are insignificant to the user acceptance of Neobanks. Furthermore, this research provides some implications for Neobanks service providers to enhance the current Neobanks app . Lastly, this research also presents several limitations of this study and offers some recommendations to provide more accurate and realistic research for future researchers.